Pengaruh penggunaan media berbasis IT dan kompetensi pedagogik guru terhadap hasil belajar siswa di gugus 3 Kecamatan Pamulihan pada masa pandemi covid-19 - Darwati , Aan (ARKA INSTITUTE, 2022)
Learning outcomes obtained by students, especially in class VI mathematics subjects have decreased. Therefore, the role of the teacher when improving pedagogic abilities (planning, implementing and evaluating learning) and the use of IT-based media (Google Classroom) is one way to improve online learning, when learning is done well automatically the learning outcomes obtained by students will good. The method used in this research is an explanatory survey research method. Meanwhile, for the population in this study, Grade 6 students were indicated to have been able to fill out the questionnaire independently. There are 307 grade 6 students from 8 elementary schools in Cluster 3, Pamulihan Subdistrict and are registered at Dapodik as active students. The sample is 76 students through the sampling technique using the proportionate stratified random sampling technique. The results of this study reveal that there is a significant influence between the use of media and the pedagogic competence of IT-based teachers on learning outcomes. This means that the variable of using IT-based media and the variable of teacher pedagogic competence simultaneously has a significant and positive impact on learning outcomes